PELATIHAN OLAHAN TEMPE BAGI WARGA PKK DESA DRONO, KLATEN - Lewerissa, Karina Bianca; Mawarno, Binardo Adiseno (Universitas Mataram, 2024)
Drono Village, Klaten Regency, Central Java, has the potential as a tempe-producing center. Unfortunately, the skills possessed by tempeh artisans are still limited, and they can only make tempeh withouth further processing diversification. Community Service Activities (PkM) are aimed at PKK members who are tempeh artisans to gain knowledge and skills regarding several types of processed tempeh, namely tempeh katsu and tempeh brownies. The activity method was carried out by providing modules several weeks before the training, distributing questionnaires regarding tempeh processing before the activity, carrying out tempeh processing practices, and assessing participants' understanding and satisfaction by distributing surveys. The activity ended with tasting the processed tempeh products that were produced together. Based on the questionnaire distributed, the participants agreed that they had gained additional knowledge regarding tempeh processing. This activity was also considered beneficial, and all participants were satisfied with their community service activities. The PKK community considers this activity essential and can be repeated with other tempeh-processing food training. They also want to apply the knowledge gained as processed products that can be sold or for family consumption.